(3HMGQ GdCfhGQ aj HjGf eG GMJL Gddg SHMGfg hQShdg hMLLg Ydi GdeNGdajf hGdeYGfOjf ef CQHGH Gdedd GdeNJdaI hGdYbGFO GdRGFaI Yf GdOjf GdeHjfs - (3GdCUagGfj, GdeLdSj, eMeO HGbQ Hf eMeO Jbj Hf ebUhO Ydj, J (B1111 (3g`s ((3eMeO Hf eMeO SYjO GdbGVjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj Ndb GdEfSGf hYdeg GdHjGf (B.. (3agPG gh GdeLdO GdQGHY ef cJGH (B..(3hGf aQbJ CLRGFg Ydi GdCHhGH GdefGSHI dgG JjSjQG ddWGdHjf (B.. (3HGH GMJLGL Gddg JYGdi Ydi CQHGH Gdedd GdeJNdaI aj GdbQBf GdcQje (B...s
(3BNQgG (B:s
.. (3agPG bhd CHj GdMSf Ydjg GdSdGe hMLJg aj faj GdQDjI hYdjgG GYbO LejY ef fai GdQDjI ef GdeJcdejf hcPdc GdNHQ GdeQhj Yf GdQVG Ydjg GdSdGe (B... (3hdfcJa aj gPG GdeLdO HeG GhQOfGs
(3Yf fSNI HNW GdeDda , GdJj gj HJGQjN QHjY GdKGfj (B1086 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\48s
(3GdPQjYI (B3\43s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdMOjK hGdeUWdMs